Adsorption Properties of Coriander Seed Powder (): Extraction and Pre-concentration of Pb(II), Cu(II) and Zn(II) Ions from Aqueous Solution - Rifaqat Ali Khan Rao; M. Kashifuddin (Adsorption Science & Technology)
Coriander seed powder has been shown to exhibit a remarkable adsorption potential towards Pb(II), Cu(II) and Zn(II) ions from aqueous solution, with the adsorption capacities following the order Pb(II) > Cu(II) > Zn(II). The influences of pH, initial metal ion concentration, adsorbent dosage and contact time on the process were investigated. The adsorption data at different temperatures were well fitted by the Langmuir, Freundlich, Temkin and Dubinin–Radushkevich (D–R) model isotherms. The kinetic data obeyed the pseudo-second-order kinetic model. The thermodynamic parameters showed that the adsorption of Pb(II) ions was endothermic and spontaneous. Competitive adsorption in the Pb(II)–Cu(II) and Pb(II)–Zn(II) systems was also studied. The breakthrough capacities of Pb(II), Cu(II) and Zn(II) ions in single metal ion systems were higher than in multi-metal ion systems. The analytical application of the adsorption process was demonstrated by the removal of Pb(II) ions from the wastewater derive from the manufacture of lead acid batteries. Excellent results were obtained when desorption of the studied metal ion from very dilute solution was effected by column methods. Hence, these methods were further utilized for the extraction and pre-concentration of Pb(II), Cu(II) and Zn(II) ions from very dilute synthetic mixtures of these metal ions prepared in doubly distilled water as well as in tap water to enable their subsequent determination by atomic absorption spectrometry.